Severe Mitral Regurgitation–Induced Acute Heart Failure due to Nonbacterial Thrombotic Endocarditis in a Patient With Urothelial Carcinoma Recurrence - Catarina Santos Reis; Francisco Dias; Bárbara Granja; Maria Inês Matos; Ana Ribeiro; Fernando Friões (Case Reports in Oncological Medicine)
Nonbacterial thrombotic endocarditis is a rare condition characterized by the formation of noninfectious vegetations on the heart valves. It is related with systemic embolic phenomena occurring predominantly in advanced cancer stages, particularly adenocarcinomas. It is a diagnosis of exclusion based on the clinical context, echocardiographic findings of a vegetation, and negative blood cultures, and distinction between infective endocarditis is challenging. We report a case of a 66-year-old woman, with history of previously treated breast and urothelial carcinoma, presenting with constitutional syndrome and pulmonary thromboembolism. Computed tomography scan revealed systemic embolic phenomena and retroperitoneal lymphadenopathies. A vegetation in the mitral valve constituted a finding on echocardiography, causing severe mitral regurgitation, which led to severe acute heart failure and culminated in patient’s death. Subsequent results of immunohistochemistry of the lymph node biopsy yielded the recurrence of urothelial carcinoma.